BANKING MODEL AND MONETARY TRANSMISSION MECHANISM IN INDONESIA: ARE ISLAMIC BANKS MORE EFFECTIVE? - Ilhamdi, Ilhamdi; Luqman, Luqman; Ali, Jati Kusuma (ASY SYAR’IYYAH: JURNAL ILMU SYARI’AH DAN PERBANKAN ISLAM, 2024)
Economic growth, both global and national, is slowing down, prompting monetary authorities to issue effective monetary policies through credit lines to encourage economic growth. In the dual banking system where there are Islamic banks and conventional banks, it is a challenge for the monetary authorities to see the effectiveness of the two banks in transmitting monetary policy. To find out the difference in effectiveness levels, the researcher used quarterly data from Bank Indonesia interest rate variables, gross domestic product (GDP), Islamic bank financing, and conventional bank loans for the period 2014 to 2024. Using VAR-ECM analysis, it was found that Islamic banks have a lower response than conventional banks in transmitting monetary policy through credit channel. In addition, Syrian banks also have lower effectiveness than conventional banks in encouraging economic growth in Indonesia.